2008
DOI: 10.1172/jci35067
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance-associated protein 4 regulates cAMP-dependent signaling pathways and controls human and rat SMC proliferation

Abstract: The second messengers cAMP and cGMP can be degraded by specific members of the phosphodiesterase superfamily or by active efflux transporters, namely the multidrug resistance-associated proteins (MRPs) MRP4 and MRP5. To determine the role of MRP4 and MRP5 in cell signaling, we studied arterial SMCs, in which the effects of cyclic nucleotide levels on SMC proliferation have been well established. We found that MRP4, but not MRP5, was upregulated during proliferation of isolated human coronary artery SMCs and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 58 publications
6
103
0
Order By: Relevance
“…MRP4 (ATP-binding cassette sub-family C member 4 [ABCC4]) is a member of the multidrug resistance proteins (MRPs) belonging to the C group of the ATP-binding cassette (ABC) protein superfamily, which functions as an energy-dependent, transmembrane efflux transporter. Compelling evidence supports that cAMP extrusion through MRP4 in several cell types provides a complementary mechanism to the phosphodiesterases (PDEs) as modulators of the intracellular concentration of the second messenger (6)(7)(8)(9)(10). In isolated pancreatic acini, we found that secretin-induced cAMP is extruded by ANF through NPR-C receptors coupled to the PLC/PKC pathway, thus restricting its intracellular accumulation.…”
Section: Introductionmentioning
confidence: 56%
“…MRP4 (ATP-binding cassette sub-family C member 4 [ABCC4]) is a member of the multidrug resistance proteins (MRPs) belonging to the C group of the ATP-binding cassette (ABC) protein superfamily, which functions as an energy-dependent, transmembrane efflux transporter. Compelling evidence supports that cAMP extrusion through MRP4 in several cell types provides a complementary mechanism to the phosphodiesterases (PDEs) as modulators of the intracellular concentration of the second messenger (6)(7)(8)(9)(10). In isolated pancreatic acini, we found that secretin-induced cAMP is extruded by ANF through NPR-C receptors coupled to the PLC/PKC pathway, thus restricting its intracellular accumulation.…”
Section: Introductionmentioning
confidence: 56%
“…PT cells obtained from the diabetic and control mice showed a rather similar DNA methylation patterns, but the methylation pattern significantly differed among the eight genes with potentially functional roles (Table 1, Supplemental Figure 3). [16][17][18][19][20][21][22][23][24] Quantitative RT-PCR analysis demonstrated that the mRNA expressions of these genes in the PT cells were significantly different between the diabetic and control mice ( Table 1, Supplemental Figure 3). An inverse correlation between expression and methylation was seen at these loci except for Met.…”
Section: Purification Of Pt Cells Andmentioning
confidence: 99%
“…7 Interestingly, a recent study describes that knockdown of MRP4 in smooth muscle cells increases cAMP and cGMP intracellular levels and blocks cell proliferation. 9 However, the functional relevance of MRP4 in smooth muscle relaxation has not been explored yet.…”
mentioning
confidence: 99%